Influence of flow rate variation on the development of Escherichia coli biofilms - J. M. R. Moreira (2013)
This work investigates the effect of flow rate variation on mass transfer and on the development of Escherichia coli biofilms on a flow cell reactor under turbulent flow conditions. Computational fluid dynamics (CFD) was used to assess the applicability of this reactor for the simulation of industrial and biomedical biofilms and the numerical results were validated by streak photography. Two flow rates of 374 and 242 L h(-1) (corresponding to Reynolds numbers of 6,720 and 4,350) were tested and wall shear stresses between 0.183 and 0.511 Pa were predicted in the flow cell reactor. External mass transfer coefficients of 1.38 x 10(-5) and 9.64 x 10(-6) m s(-1) were obtained for the higher and lower flow rates, respectively. Biofilm formation was favored at the lowest flow rate because shear stress effects were more important than mass transfer limitations. This flow cell reactor generates wall shear stresses that are similar to those found in some industrial and biomedical settings, thus it is likely that the results obtained on this work can be used in the development of biofilm control strategies in both scenarios.